Analisis Kebutuhan Karyawan Bagian Teknisi Migrasi Berdasarkan Beban Kerja Pada PT. Telkom Regional Samarinda - Hendra Nur Eko Saputro; Djoko Setyadi; Robiansyah Robiansyah (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this study was to determine the number of employees needs Migration Section Technician based measurement workload. Yan used the basic theory of human resource management using standard timing analysis tool to determine the employee's needs by using 15 samples graduation.The conclusion of this study:The standard time task completion karyaawan part PT TELKOM Regional Samarinda migration was 0.83 hours which is used to determine the number of employees of the migration needs on PT TELKOM Regional Samarinda.Based on the observation time to file nine observations amount of time needed to complete 10.86 hours, which means the need for migration on the part of employees of PT TELKOM Regional Samarinda as many as 14 groups or 28 people, employees of the migration of PT TELKOM Regional Samarinda that exist today there are 37 groups of 74 people or more means 23 groups or 46 employees of the migration of PT TELKOM Regional SamarindaKeywords: Keywords: Standard Time - Employee Needs